De Novo Genome Sequence Assemblies of Gossypium raimondii and Gossypium turneri. Issue 10 (1st October 2019) - Udall, Joshua A; Long, Evan; Hanson, Chris; Yuan, Daojun; Ramaraj, Thiruvarangan; Conover, Justin L; Gong, Lei; Arick, Mark A; Grover, Corrinne E; Peterson, Daniel G; Wendel, Jonathan F
Abstract: Cotton is an agriculturally important crop. Because of its importance, a genome sequence of a diploid cotton species ( Gossypium raimondii, D-genome) was first assembled using Sanger sequencing data in 2012. Improvements to DNA sequencing technology have improved accuracy and correctness of assembled genome sequences. Here we report a new de novo genome assembly of G. raimondii and its close relative G. turneri . The two genomes were assembled to a chromosome level using PacBio long-read technology, HiC, and Bionano optical mapping. This report corrects some minor assembly errors found in the Sanger assembly of G. raimondii . We also compare the genome sequences of these two species for gene composition, repetitive element composition, and collinearity. Most of the identified structural rearrangements between these two species are due to intra-chromosomal inversions. More inversions were found in the G. turneri genome sequence than the G. raimondii genome sequence. These findings and updates to the D-genome sequence will improve accuracy and translation of genomics to cotton breeding and genetics.